Les femmes musulmanes et le « droit de choisir librement » - Abu-Lughod, Lila (Anthropologie et Sociétés, 2018)
Tout en soulignant qu’il s’avère illusoire de vouloir séparer les situations personnelles des conditions historiques et politiques de leur émergence, cet article propose une réflexion critique de la notion de libre choix, que l’auteure inscrit dans un réseau de facteurs macrosociaux tels que les tensions internationales ou encore la violence et la pauvreté structurelles. La notion de « libre choix » possède une charge idéologique qui se reflète dans la distinction souvent établie entre les femmes occidentales libérées et la femme musulmane dépourvue de libre choix et victime passive de l’oppression patriarcale. Le libre choix tend aujourd’hui à (re)devenir un critère discriminatoire permettant de distinguer les sociétés les « plus civilisées » (choix et liberté pour les « Occidentales ») de celles qui le sont moins (contrainte et servitude pour les « Orientales »). La violation du libre choix des femmes peut alors contribuer à légitimer l’intervention des industries humanitaire et militaire pour « sauver les musulmanes », comme cela a été le cas dans la guerre d’Afghanistan, à la suite des événements tragiques du 11 septembre 2001. Qui a le pouvoir de réduire « l’Autre », et particulièrement les musulmanes, à des sujets assujettis incapables d’émerger comme sujets agissants ? Des musulmanes souffrent d’un libre choix limité, mais ceci est-il réductible à l’islam ? Le libre choix des Occidentales relève-t-il d’un idéal fantasmé ? Faudrait-il plutôt investiguer la notion de libre choix dans sa complexité intrinsèque reliée aux relations de pouvoir ? Réduire les vies poignantes et tellement complexes des femmes musulmanes à une question de choix plus ou moins libre et éclairé est d’une totale insatisfaction pour l’anthropologue. Afin de mieux saisir cette complexité, l’auteure puise dans son travail ethnographique s’échelonnant sur une vingtaine d’années en milieu rural égyptien pour souligner l’importance du travail (micro)ethnographique qui permet de dépasser les généralités et les simplicités galvaudées par certains médias et romans à sensation (« pulp nonfiction ») qui font et défont l’opinion publique. L’auteure compare ces généralités essentialisantes avec des exemples de vies socialement complexes et ethnographiquement riches de villageoises égyptiennes.
Keywords: afrique; anthropologie; approches et analyses; corps; cours; discipline; féminisme décolonial; féminisme islamique; pol4212; premier cycle; racisme; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; égypte

Geographies of privilege - Twine, France Winddance; Gardener, Bradley (Routledge, 2013)
How are social inequalities experienced, reproduced and challenged in local, global and transnational spaces? What role does the control of space play in distribution of crucial resources and forms of capital (housing, education, pleasure, leisure, social relationships)? The case studies in Geographies of Privilege demonstrate how power operates and is activated within local, national, and global networks. Twine and Gardener have put together a collection that analyzes how the centrality of spaces (domestic, institutional, leisure, educational) are central to the production, maintenance and transformation of inequalities. The collected readings show how power--in the form of economic, social, symbolic, and cultural capital--is employed and experienced. The volume's contributors take the reader to diverse sites, including brothels, blues clubs, dance clubs, elite schools, detention centers, advocacy organizations, and public sidewalks in Canada, Italy, Spain, United Arab Emirates, Mozambique, South Africa, and the United States. Geographies of Privilege is the perfect teaching tool for courses on social problems, race, class and gender in Geography, Sociology and Anthropology.
Keywords: afrique; afrique du sud; amériques; anthropologie; approches et analyses; canada; classe sociale; discipline; environnement; espagne; europe; géographie; italie; mozambique; outils; ouvrages de références; privilèges; racisme; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; émirats arabes unis; états-unis

Lost boys, invisible girls: stories of Sudanese marriages across borders - Grabska, Katarzyna (Gender, Place & Culture, 2010)
Forced migration challenges and changes gender relations. The transnational activities of refugees resettled in the West create gender asymmetries among those who stay behind. This article explores the transnational marriages of young southern Sudanese women (‘invisible girls’), who either stayed in Sudan or remained in refugee camps in Kenya, to Sudanese men who were resettled to America, Canada or Australia (‘lost boys’). Incorporating gender as a relational category into the analysis of transnational practices that migrants and refugees engage in is important. The article argues that there is a need to put feminist analysis at the centre of transnational processes resulting from (forced) migration. It looks at the connections between different geographical locations, the impacts of the migration of young refugee men on bridewealth and marriage negotiations and the gender consequences for young women, men and their families. It is argued that transnational activities, such as marriage, contest, reconfigure and reinforce the culturally inscribed gender norms and practices in and across places. Transnational marriage results in ambiguous benefits for women (and men) in accessing greater freedoms. Anthropological analyses of marriage need a geographical focus on the transnational fields in which they occur. The article seeks to deepen understanding of the nuanced gendered consequences of transnationalism. It shows how gender analysis of actions taken across different locations can contribute to the theorisation of transnational studies of refugees and migrants.
Keywords: 2000 à aujourd'hui; 2000-2009; afrique; amériques; anthropologie; anthropologie sociale; approches et analyses; australie; canada; cours; discipline; histoire et politique; kenya; mariage; migration; océanie; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sex2283; sexisme; soudan; systèmes d'oppressions; thématiques; transnationalisme; états-unis

Transcultural bodies: female genital cutting in global context - Hernlund, Ylva; Shell-Duncan, Bettina (Rutgers University Press, 2007)
Female "circumcision" or, more precisely, female genital cutting (FGC), remains an important cultural practice in many African countries, often serving as a coming-of-age ritual. It is also a practice that has generated international dispute and continues to be at the center of debates over women's rights, the limits of cultural pluralism, the balance of power between local cultures, international human rights, and feminist activism. In our increasingly globalized world, these practices have also begun immigrating to other nations, where transnational complexities vex debates about how to resolve the issue. Bringing together thirteen essays,Transcultural Bodiesprovides an ethnographically rich exploration of FGC among African diasporas in the United Kingdom, Europe, and Australia. Contributors analyze changes in ideologies of gender and sexuality in immigrant communities, the frequent marginalization of African women's voices in debates over FGC, and controversies over legislation restricting the practice in immigrant populations.
Keywords: afrique; anthropologie; approches et analyses; australie; corps; cours; discipline; europe; histoire et politique; océanie; premier cycle; racisme; ressource en ligne; royaume-uni; régions géographiques; santé; sciences humaines; sex2283; sexisme; sexualité; sociologie; système colonial; systèmes d'oppressions; thématiques; transculturalisme; violences